Penanaman Pendidikan Karakter Melalui Lagu Anak Pada Anak Kelompok A Di Tk Aisyiyah Pucangan 1 KartasuraTahun Ajaran 2016/ 2017 - Wijayanti, Astrilia; , Drs. Amrul Choiri, M.Ag (2017)
ABSTRACT The purpose of this research is to know the effect of nursery rhyme to the investing of character education for children in Group A at TK Aisyiyah in Pucangan 1 Kartasura. This research was experimental research. The research Experimental design used was pre-experimental design that used one group pretest-posttest design. The subject in this research was 16 children from Group A. The data collection techniques in this research was conducted through interview, test, documentation, observation, namely nonparticipant observation. The data were analyzed through t-test. The result was the investing of character education for children Group A was 13,75 average value for pretest and 19,5 average value for posttest. The result of T-test analysis used program SPSS 16.0 for Windows was that paired sample t-test obtained t -15.057 <- ttable is -1.753 the result is that H0 is rejected and Ha is received. The conclusion of the research is that there is of the using of nursery rhyme influences the character education for children in Group A at TK Aisyiyah in Pucangan 1 Kartasura. Keywords: Character Education, Nursery Rhyme.